2015
DOI: 10.1039/c5gc01473e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative conversion of lignin and lignin model compounds catalyzed by CeO2-supported Pd nanoparticles

Abstract: † Electronic Supplementary Information (ESI) available: [XPS spectra, H2chemsorption results, HPLC spectra of products from Organosolv lignin conversion, effects of O2 pressure for the conversion of PP-ol, conversion of PP-one under N2 and O2, conversion of methanol under N2, and the catalytic performances of CeO2 supported Au and Pt catalysts]. SeeThe oxidative transformation of lignin into aromatic compounds is an attractive route for chemical utilization of lignocellulosic biomass. Unlike hydrogenolysis, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
170
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 70 publications
(21 reference statements)
2
170
0
Order By: Relevance
“…This approach has been applied to wood pulp delignification, in which oxidation of the C a alcohol to a ketone favours the breakdown of b-O-4 linkages. Wang et al [85] also reported a bifunctional Pd/CeO 2 catalyst able to efficiently cleave b-O-4 bonds in the presence of C a -hydroxyl group, in which synergy between palladium activation of the oxidant and the redox properties of ceria facilitates b-O-4 cleavage; Pd is widely used in heterogeneous catalysis for aerobic alcohol oxidation [86][87][88][89][90]. This bifunctional catalyst was able to transform a range of Organosolv lignin in ethanol under oxygen to vanillin, guaiacol, and 4-hydroxybenzaldehyde.…”
Section: Oxidative Transformationsmentioning
confidence: 99%
“…This approach has been applied to wood pulp delignification, in which oxidation of the C a alcohol to a ketone favours the breakdown of b-O-4 linkages. Wang et al [85] also reported a bifunctional Pd/CeO 2 catalyst able to efficiently cleave b-O-4 bonds in the presence of C a -hydroxyl group, in which synergy between palladium activation of the oxidant and the redox properties of ceria facilitates b-O-4 cleavage; Pd is widely used in heterogeneous catalysis for aerobic alcohol oxidation [86][87][88][89][90]. This bifunctional catalyst was able to transform a range of Organosolv lignin in ethanol under oxygen to vanillin, guaiacol, and 4-hydroxybenzaldehyde.…”
Section: Oxidative Transformationsmentioning
confidence: 99%
“…[6] Cleavage of the b-O-4 linkager equires ab ond dissociation energy (BDE) of 54-72 kcal mol À1 . [3,6,[9][10][11] The two-step strategy of preoxidation and cleavage of the b-O-4 bond for lignin depolymerization can be performed under milderc onditions butu sually requires additional reductants/oxidants or acids/bases and generates large amountso fb yproducts. [3,6,[9][10][11] The two-step strategy of preoxidation and cleavage of the b-O-4 bond for lignin depolymerization can be performed under milderc onditions butu sually requires additional reductants/oxidants or acids/bases and generates large amountso fb yproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these challenges, the biomass pretreatment methodology or lignin-first concept was developed to provide an opportunity to realizet he full utilization of the three componentsinl ignocellulosic biomass. Supported metal catalysts including Pd, [12] Co, [13] Cu, [14] and V [15] gave For soft lignocellulose (pine), lignin was first decomposed into guaiacol and phenol with yields of 15.3 and 12.9 %a t9 8.6 % delignificatione fficiency at 130 8Cf or 14 h. Meanwhile, hemicellulose andc ellulose were intact during the delignifying process and were subsequently hydrolyzed to 3.5 %x ylose at 100 %h emicellulosec onversion efficiency at 150 8Cf or 14 h and 36.4 %g lucose at 100 %c ellulose conversion efficiency at 170 8Cf or 12 h, respectively.F or hard lignocellulose (poplar), the yields of guaiacol and phenol were 10.1 and 8.7 %a t 91.9 %d elignification efficiency at 130 8Cf or 14 h, whereas 12.9 %x ylose at 90.4 %h emicellulose conversion efficiency at 150 8Cf or 12 ha nd 32.9 %g lucose at 100 %c ellulose conversion efficiency at 170 8Cf or 12 hw ere obtained. Amongt he linkages, the b-O-4 motif is considered as the typical unit and the most abundant linkage, which composes up to 70 %o fl ignin.…”
Section: Introductionmentioning
confidence: 99%